2021
DOI: 10.1177/21582440211050385
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Used and Challenges Faced by Thai EFL Teachers When Eliciting Talk During Classroom Interactions in High School Contexts

Abstract: Utilizing Conversation Analysis, this study examined classroom interactions to identify strategies secondary school teachers used to elicit EFL learners’ talk in four micro-pedagogical contexts. How strategies were used, and the challenges teachers faced were also explored. Four Thai teachers of English participated in the study, and approximately 7 hours of video and audio recordings were transcribed and analyzed alongside semi-structured teacher interviews. Overall, the most prevalent strategy used to elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The findings point toward the crucial role of clarity in stating lesson objectives and instructions in this process. While this finding is in line with previous research Murray et al, 2012), some teachers added that using the L1 can help to clarify instructions for low-level students, which is also supported by previous studies (Farrelly & Sinwongsuwat, 2021). The findings further reflect the importance of providing online resources to promote the learning community (Hersman & Schroeder, 2017).…”
Section: Strategies That Promote Student-content Interactionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings point toward the crucial role of clarity in stating lesson objectives and instructions in this process. While this finding is in line with previous research Murray et al, 2012), some teachers added that using the L1 can help to clarify instructions for low-level students, which is also supported by previous studies (Farrelly & Sinwongsuwat, 2021). The findings further reflect the importance of providing online resources to promote the learning community (Hersman & Schroeder, 2017).…”
Section: Strategies That Promote Student-content Interactionsupporting
confidence: 90%
“…Finally, using the L1 to clarify instructions was rated the lowest in this category, which is inconsistent with prior findings. Farrelly and Sinwongsuwat (2021) found that the use of L1 helps students to understand new concepts in second language classes. It seems that students understand the importance of language practice, which may be why there is variance in students" responses.…”
Section: Students' Perceptions Of Strategies That Promote Student-con...mentioning
confidence: 99%
“…Thus, a novice teacher should consider how to use his TT to elicit students to engage in classroom activities rather than merely lecturing students and taking them as passive learners. Display questioning, scaffolding strategies and referential questioning are three prevalent strategies that could be used to motivate learners to participate in EFL classroom(Farrelly & Sinwongsuwat, 2021). Farrelly and Sinwongsuwat (2021) also mentioned anticipated problems include that learners fail to give response, prefer to be passive receiver, give selective answering, etc.…”
mentioning
confidence: 99%